Kajian Penerapan Model Teologi Kontekstual - Handoyo Kusumahadi; Iskak Sugiyarto (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study analyzes the ministry practices and doctrines of JKI The Rock Church, a charismatic church that bases its activities on the direction of the Holy Spirit. This approach often generates controversy, particularly due to unique practices such as "Coffin Baptism" aimed at mortifying the desires of the flesh. Although this practice is considered heretical by other churches, it opens up unexpected evangelistic opportunities within the community. Furthermore, this church demonstrates flexibility in contextualizing its ministry by actively interacting with community organizations and cultural activities. The church's pastor, Rev. Amos, implements inculturation by integrating local cultural values, such as Javanese arts and traditions, into church services and events. The goal is to build bridges with various community groups, including Muslims, to create evangelistic opportunities and be a blessing. Based on this analysis, it is concluded that Bevans' contextual theology model is highly relevant to understanding this church's holistic approach. This model emphasizes that no single approach is absolutely correct, but rather the need for synergistic interaction between various models to address contextual issues comprehensively and effectively.